Ancient Egyptian Scarabs. - Newberry (Taylor and Francis, 2012)
The seals collected by Captain Timins of Cairo are here catalogued, reproduced and described by Percy Newberry to make an attractive and useful book. The original collector chose on the basis of historic, as well as artistic merit, to form his choice. The provenance of the seals is mostly from the Eastern Delta and Upper Egypt.